Gold-catalyzed 1,2-oxyalkynylation of N-Allenamides with ethylnylbenziodoxolones - Banerjee, Somsuvra; Senthilkumar, Beeran; Patil, Nitin T. (Organic Letters, 2019)
A gold-catalyzed 1,2-oxyalkynylation of N-allenamides with ethylnylbenziodoxolones (EBXs) has been achieved for the first time. The reaction, which follows a redox-neutral Au(I)/Au(III) catalytic pathway, was enabled in an attempt to exhaust the EBX reagents atom-economically by putting the nucleophilic carboxylate part of EBXs to appropriate use. This constitutes the first example for gold-catalyzed beta-alkynylation of N-allenamides to construct highly valuable 1,3-enynes. The potential of the sequence is further documented by some follow-up transformations.

Gold and hypervalent iodine(iii): liaisons over a decade for electrophilic functional group transfer reactions - Banerjee, Somsuvra; Bhoyare, Vivek W.; Patil, Nitin T. (Chemical Communications, 2020)
Over the last two decades, hypervalent iodine(iii) reagents have evolved from being `bonding curiosities' to mainstream reagents in organic synthesis, in particular, electrophilic functional group transfer reactions. In this context, gold catalysts have not only emerged as a unique toolbox to facilitate such reactions (especially alkynylations) but also opened new possibilities with their different modes of reactivities for other functional group transfer reactions (acetoxylations and arylations). This feature article critically summarizes hitherto all such Au-catalyzed electrophilic functional group transfer reactions with hypervalent iodine(iii) reagents, emphasizing their mechanistic aspects.

Gold-catalyzed alkynylative meyer-schuster rearrangement - Banerjee, Somsuvra; Ambegave, Shivhar B.; Mule, Ravindra D.; Senthilkumar, Beeran; Patil, Nitin T. (Organic Letters, 2020)
By applying the ``interplay'' mode, which consolidates two key reactivity modes of gold catalysis, namely pi-activation mode and cross-coupling mode, the first alkynylative Meyer-Schuster rearrangement is designed and successfully implemented. The current protocol gives straightforward access to enynones, a highly valuable building block, from easily available propargyl alcohol feedstocks. Control experiments suggest an Au(III) catalyst triggers the Meyer-Schuster rearrangement, whereas monitoring the reaction with ESI-HRMS provided strong evidence in favor of a key alkynylgold(III) intermediate which supports the proposed ``interplay'' scenario.